Equine Histoplasmosis in Ethiopia: Phylogenetic analysis by sequencing of the internal transcribed spacer region of rRNA genes - Ameni, G.; Messele, A.; Zewude, A.; Girma, M.; Asfa, R.; Mamo, M.; Kyallo, Martina M.; Stomeo, Francesca; Gumi, B.; Sori, T. (Frontiers Media, 2022)
Equine histoplasmosis commonly known as epizootic lymphangitis (EL) is a neglected granulomatous disease of equine that is endemic to Ethiopia. It is caused by Histoplasma capsulatum variety farciminosum, a dimorphic fungus that is closely related to H. capsulatum variety capsulatum. The objective of this study was to undertake a phylogenetic analysis of H. capsulatum isolated from EL cases of horses in central Ethiopia and evaluate their relationship with H. capsulatum isolates in other countries and/or clades using the internal transcribed spacer (ITS) region of rRNA genes. Clinical and mycological examinations, DNA extraction, polymerase chain reaction (PCR), Sanger sequencing, and phylogenetic analysis were used for undertaking this study. Additionally, sequence data of Histoplasma isolates were retrieved from GenBank and included for a comprehensive phylogenetic analysis. A total of 390 horses were screened for EL and 97 were positive clinically while H. capsulatum was isolated from 60 horses and further confirmed with PCR, of which 54 were sequenced. BLAST analysis of these 54 isolates identified 29 H. capsulatum isolates and 14 isolates from other fungal genera while the remaining 11 samples were deemed insufficient for further downstream analysis. The phylogenetic analysis identified five clades, namely, African, Eurasian, North American 1 and 2, and Latin American A and B. The Ethiopian isolates were closely aggregated with isolates of the Latin American A and Eurasian clades, whereas being distantly related to isolates from North American 1 and 2 clades as well as Latin American B clade. This study highlights the possible origins and transmission routes of Histoplasmosis in Ethiopia.